Analysis of dissertation works on physical education and sport for period from 1998 to 2008 - Andriychuk O.Y; Grygus I.M (Kharkov National Pedagogical University, 2010)
Dissertation works of competitors of scientific degree of doctor and candidate of sciences are analyzed after specialities Olympic and professional sport, physical culture, physical education of different groups of population, physical rehabilitation and medical rehabilitation. Concentrated attention on basic directions of researches in industry of physical education and sport after scientific specialties, contingents investigated, their problems and ways of decision, state of health, dynamics of defence of dissertation researches.